theorem zmodeqmod (a b n: nat): $ n != 0 -> (a %Z n = b %Z n <-> modZ(n): a = b) $;
Step | Hyp | Ref | Expression |
---|---|---|---|
1 |
b0 (a %Z n) = b0 (b %Z n) -> modZ(n): b0 (a %Z n) = b0 (b %Z n) |
||
2 |
a %Z n = b %Z n -> b0 (a %Z n) = b0 (b %Z n) |
||
3 |
a %Z n = b %Z n -> modZ(n): b0 (a %Z n) = b0 (b %Z n) |
||
4 |
a %Z n % n = a %Z n |
||
5 |
b %Z n % n = b %Z n |
||
6 |
modZ(n): b0 (a %Z n) = b0 (b %Z n) <-> mod(n): a %Z n = b %Z n |
||
7 |
conv eqm |
modZ(n): b0 (a %Z n) = b0 (b %Z n) <-> a %Z n % n = b %Z n % n |
|
8 |
modZ(n): b0 (a %Z n) = b0 (b %Z n) -> a %Z n % n = b %Z n % n |
||
9 |
modZ(n): b0 (a %Z n) = b0 (b %Z n) -> a %Z n = b %Z n |
||
10 |
a %Z n = b %Z n <-> modZ(n): b0 (a %Z n) = b0 (b %Z n) |
||
11 |
n != 0 -> modZ(n): b0 (a %Z n) = a |
||
12 |
n != 0 -> modZ(n): b0 (b %Z n) = b |
||
13 |
n != 0 -> (modZ(n): b0 (a %Z n) = b0 (b %Z n) <-> modZ(n): a = b) |
||
14 |
n != 0 -> (a %Z n = b %Z n <-> modZ(n): a = b) |